2019
DOI: 10.1002/bjs5.50148
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal pain and symptoms before and after Roux‐en‐Y gastric bypass

Abstract: Background Despite increased emphasis on patient‐reported outcomes, few studies have focused on abdominal pain symptoms before and after Roux‐en‐Y gastric bypass (RYGB). The aim of this study was to quantify chronic abdominal pain (CAP) in relation to RYGB. Methods Patients with morbid obesity planned for RYGB were invited to participate at a tertiary referral centre from February 2014 to June 2015. Participants completed a series of seven questionnaires before and 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
3
29
1
2
Order By: Relevance
“…The observed improvements in the physical functioning aspects of HRQoL after RYGB have previously been described [9, 12]. However, we are the first to describe that the improved physical functioning is irrespective of the presence of IBS-like symptoms after RYGB.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The observed improvements in the physical functioning aspects of HRQoL after RYGB have previously been described [9, 12]. However, we are the first to describe that the improved physical functioning is irrespective of the presence of IBS-like symptoms after RYGB.…”
Section: Discussionsupporting
confidence: 66%
“…Both constipation and diarrhea symptoms increased after RYGB, with a comparable mean change in participants with and without IBS at the preoperative visit. Previous studies have shown diverging dynamics of these symptoms after RYGB [12, 28, 29]. However, although statistically significant, the absolute changes in mean diarrhea and constipation symptom score are unlikely to be of high clinically importance (< 15% increase in symptom score), with exception of the subgroup of participants with new onset of IBS-like symptoms after RYGB who experienced a mean 33% increase for both diarrhea and constipation symptom scores.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We do not have preoperative data, and the preoperative symptom burden may have been high. We have recently published before and after RYGB data reporting similar GSRS scores in 28.1% patients two years after surgery [19]. In another study, we found that 32.8% of the patients reported bothersome abdominal pain symptoms 5 years after RYGB [20].…”
Section: Discussionmentioning
confidence: 68%
“…Long-term evaluations on gastrointestinal symptoms after RYGB are limited. We have previously observed high rates of such symptoms 2 and 5 years after RYGB [ 19 , 20 ]. Long-term evaluations and knowledge of such symptoms may improve the quality of health care for these patients.…”
mentioning
confidence: 99%